Translating restrictive law into practice: an ethnographic exploration of the systemic processing of legally restricted health care access for asylum seekers in Germany - Ziegler, Sandra; Bozorgmehr, Kayvan (International journal for equity in health, 2024)
Access to health services for asylum seekers is legally restricted in Germany. The law is subject to interpretation, therefore the chance of receiving care is not equally distributed among asylum seekers. What services are provided to whom is ultimately decided by health professionals and government employees. The respective prioritization processes and criteria are not transparent. We sought to understand how legal restrictions are translated into daily practices and how this affects the health system. We aimed to outline the complex process of cost coverage for health services for asylum seekers and provide insights into common decision-making criteria.
Gesehen am 10.04.2025